Satisfaction with HIV/AIDS treatment and care services and its associated factors among adult people receiving antiretroviral therapy in Ethiopia: a systematic review and meta-analysis - Tizalegn Tesfaye Mamo; Mesfin Abebe; Habtamu Endashaw Hareru; Zemachu Ashuro; Berhanu G Debela; Daniel Sisay; Eden Ashenafi (BMJ Open, 2025)
Objective To make healthcare programmes more patient-centred and efficient in light of limited resources, it is crucial to ensure patient satisfaction. There is limited information on the overall level of satisfaction with Human Immunodeficiency Virus/ Acquired Immune deficiency syndromes (HIV/AIDS) treatment and care services in Ethiopia. This meta-analysis aimed to generate a nationwide pooled estimate of the level of satisfaction with HIV/AIDS and associated factors by combining data from primary studies to provide a general overview of the effect across the country, aiming to informed policy decisions.Design Systematic review and meta-analysis.Data source PubMed, Scopus, Hinari, African journals online and Google Scholar were used to locate published studies.Eligibility criteria Observational studies assessing the level of satisfaction with HIV/AIDS care and treatment services and its associated factors among adult people living with HIV/AIDS receiving antiretroviral therapy in Ethiopia were included.Data extraction and synthesis Two authors extracted the data using a pre-established data extraction format and exported it to Stata V.17 for analysis. The Cochran-Q and I2 test statistics were used to measure the statistical heterogeneity among included studies. A random-effects meta-analysis model with the Der Simonian-Laird method was used to estimate the pooled effect size of satisfaction with HIV/AIDS care and treatment services with its 95% CI. Small study effects were assessed using Egger’s regression test at a 5% level of significance. A meta-regression analysis and a leave-one-out sensitivity analysis were also conducted.Results 24 studies were included. The pooled level of satisfaction with HIV/AIDS treatment and care services in Ethiopia was 69.7% (95% CI 63.8, 75.5%) with a significant level of heterogeneity (I2=98.0%; p<0.01). Addis Ababa city administration has the highest (83.9%; 95% CI: 79.9%, 87.9%) level of satisfaction and Southern Ethiopia has the lowest (64.5%; 95% CI: 51.3%, 77.8%). Even though variables were measured differently across primary studies and challenged to pool the effect estimates, most of the reviewed studies revealed satisfaction with HIV/AIDS care and treatment services was related to waiting times and the duration of receiving HIV/AIDS care. Moreover, this meta-analysis found gender (OR=1.11, 95% CI: 0.73, 1.69) and residence (OR=1.10, 95% CI: 0.72, 1.69) had no significant association with satisfaction with HIV/AIDS care and treatment services.Conclusions More than two-thirds were satisfied with HIV/AIDS treatment and care services in Ethiopia. The findings showed the presence of regional differences in satisfaction with HIV/AIDS treatment and care services. The finding suggested that policy-makers and healthcare administrators should focus on empowering patients to make treatment decisions, pay attention to areas of service provision that affect HIV/AIDS care and treatment services and make strategic plans for effective and better-quality services.PROSPERO registration number CRD42023438589.